Synthesis, Crystal Structure, Fluorescence and Photocatalytic Properties of a Copper Compound with 2‐Phenyl‐1H‐1, 3, 7, 8‐tetraazacyclopenta[l]phenanthrene and Silicotungstic Acid. Issue 5 (3rd March 2015) - Xu, Dongbo; Luo, Bifu; Chen, Min; Meng, Suci; Wu, Yunlong; Jiang, Deli
Abstract The polyoxometalate compound [CuPTCP(H2O)2.5]2[SiW12O40]·10.5H2O (1) was synthesized under hydrothermal conditions using 2‐phenyl‐1H‐1, 3, 7, 8‐tetraazacyclopenta[l]phenanthrene (PTCP) and Keggin‐type silicotungstic acid (H4SiW12O4) as neutral ligands. Compound 1 was characterized by single‐crystal X‐ray diffraction, elemental analysis, as well as IR and UV/Vis spectroscopy. It crystallizes in the orthorhombic space group Cmcm with a = 15.490(8) nm, b = 25.263(8) nm, c = 20.988(8) nm, α = 90°, β = 90°, γ = 90°, V = 8213(6) nm3, Z = 2. Compared with the ligand PTCP, the fluorescent spectra of compound 1 are different. Furthermore, the Rhodamine B (RhB) photodegration process by compound 1 as catalyst was studied. It could be shown that the DR% of compound 1 is more than twice that of pure silicotungstic acid.